Effects of Gap on Erosion Surrounding Culvert Joints - An Experimental Study - Kuswari, Sari; Hardiyatmo, Hary Christady; Fathani, Teuku Faisal (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2024)
Culvert is one of the drainage systems designed to transport water from one place to another place. Soil erosion can occur due to gaps in the joints of culverts, leading to phenomena such as piping, backward erosion, and suffusion caused by water discharge. When water flows through a gap culvert joint, it makes the soil around it fluid, which can result in sand boiling, and eventually, the formation of sinkholes. Water entrains soil particles, reducing soil density around the culvert, forming voids that expand with erosion. A laboratory-based study investigated gaps in culvert joints, and found that water flow velocity and duration significantly influence soil erosion. Water flow transports eroded materials into culverts, with most soil particles settling around the joints. The gaps of culvert joints can impact erosion, with larger gaps leading to greater influx of soil particles into the culvert. Longer flow durations also result in greater erosion, as fluidization of the soil leads to increased erosion. On the other hand, larger lengths of culvert joints result in reduced erosion. Soil accumulation along the culvert joints cover and clogging contribute to this phenomenon. Culverts lacking joints cover suffer significant erosion, with soil particles entering the culvert. Sedimentary material is predominantly found within the culvert rather than being carried out by the flow. Additionally, the size of eroded soil particles affects the width of the gaps, typically ranging from 0.25 - 0.4 mm. The erosion phenomenon that occurs around culvert joints can lead to long-term effects.